In-vitro anti-inflammatory and antioxidant potential of Triphala guggul tablets - Verma, Poonam; Singh, Baljinder; Kumar, Arun; Sharma, Ruchita; Kumar, Vijender (Journal of Medicinal Herbs and Ethnomedicine, 2020)
Current study investigated the in-vitro anti-inflammatory and antioxidant potential of successive extracts of a polyherbal formulation Lakshadi guggul tablet a combination of Indian medicinal plants viz. Commiphora mukul, Cissus quadrangularis, Laccifer lacca, Sida veronicaefolia, Terminalia arjuna and Withania somnifera. The studies were undertaken to assess the anti-inflammatory at doses levels of 200 mg and 400 mg/ml of each extract by in-vitro red blood cells membrane stabilization and antioxidant potential at doses levels of 125 μg, 250 μg and 500 μg/ml of each extract by DPPH free radical scavenging activity methods. In-vitro anti- inflammatory activity of extracts were found significant (aP<0.01, bP<0.05) red blood cells membrane stabilization effects with 66.40 % in methanol, 62.15 % in ethyl acetate, 59.39 % in chloroform extract, and 66.18% with standard drug diclofenac. Similarly, in-vitro antioxidant activity of Lakshadi guggul tablets extracts were found significant reduction in free radical scavenging activity in 49.60% in methanol, 48.10% in ethyl acetate extract and relatively similar to 52.21% of standard drugs. The results of these studies revealed that Lakshadi guggul have strong potential antioxidant and anti- inflammatory agents.